The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.ejcts.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lactate release following cardiopulmonary bypass

Abstract: The lungs were found to be a significant source of lactate, and this pulmonary lactate flux was accentuated by CPB. The PLR correlated with systemic hyperlactatemia as well as the A-a O2 gradient, and was found to be higher in patients requiring prolonged mechanical ventilatory support. The duration of CPB had a significant impact on the systemic lactate concentrations, V-A dpCO2 and the A-a O2 gradient, but not on the PLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
0
31
0
2
Order By: Relevance
“…Multivariate analysis also showed a significant correlation between these two variables. Previous studies showed that insufficient bronchial artery blood flow during CPB could result in lung tissue ischemia and pulmonary lactate release, which correlated with prolonged mechanical ventilation [29], [30]. Also, CPB causes activation of the complement system and the release of various pro-inflammatory cytokines, which results in post-CPB lung dysfunction and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis also showed a significant correlation between these two variables. Previous studies showed that insufficient bronchial artery blood flow during CPB could result in lung tissue ischemia and pulmonary lactate release, which correlated with prolonged mechanical ventilation [29], [30]. Also, CPB causes activation of the complement system and the release of various pro-inflammatory cytokines, which results in post-CPB lung dysfunction and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of pulmonary lactate release correlate well with systemic lactate levels. This lactate release is increased in procedures employing CPB and correlates with prolonged respiratory support 6. Furthermore, deflated/unventilated lungs during CPB induce atelectasis,12 which may further induce pro-inflammatory cytokine production 17.…”
Section: Discussionmentioning
confidence: 99%
“…Gasparovic et al 6 studied pulmonary lactate release and changes in ΔA–aO 2 during CPB. They reported that the lungs were a significant source of lactate release and there was a correlation between pulmonary lactate release and peripheral lactate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Dixon et al [11] found that marked prothrombotic response after CPB is associated with elevated lactate levels. Gasparovic et al [12] maintain that the lungs are an additional possible source of lactate during CPB. Besides anaerobic glycolysis, increased aerobic glycolysis by catecholamine-stimulated Na ?…”
Section: Discussionmentioning
confidence: 99%